Tin+1Cn MXenes with fully saturated and thermally stable Cl terminations. Issue 9 (16th August 2019) - Lu, J.; Persson, I.; Lind, H.; Palisaitis, J.; Li, M.; Li, Y.; Chen, K.; Zhou, J.; Du, S.; Chai, Z.; Huang, Z.; Hultman, L.; et al.
Abstract : MXenes are an extensive family of 2D transition metal carbides and nitrides, whose properties are strongly affected by surface terminations, typically O and F. Herein, we enable chlorine as a new termination, thereby expanding the property space. Abstract : MXenes are a rapidly growing family of 2D materials that exhibit a highly versatile structure and composition, allowing for significant tuning of the materials properties. These properties are, however, ultimately limited by the surface terminations, which are typically a mixture of species, including F and O that are inherent to the MXene processing. Other and robust terminations are lacking. Here, we apply high-resolution scanning transmission electron microscopy (STEM), corresponding image simulations and first-principles calculations to investigate the surface terminations on MXenes synthesized from MAX phases through Lewis acidic melts. The results show that atomic Cl terminates the synthesized MXenes, with mere residual presence of other termination species. Furthermore, in situ STEM-electron energy loss spectroscopy (EELS) heating experiments show that the Cl terminations are stable up to 750 °C. Thus, we present an attractive new termination that widely expands the MXenes' functionalization space and enables new applications.